Assessment of speed and power abilities of the students during the weekly training cycles - G.O. Pyatnychuk (Physical Education of Students, 2014)
Purpose : summarizes the current scientific literature data on the physical condition of the students during the period of study in higher education establishment and also distinguished certain manifestations of physical performance level they had during the school week. Material : the study involved 205 students of 1-5 courses at the age of 16-22 years. The levels of physical performance on the test PWC170. Results : It was found that the dynamics of physical performance depends on the period and the period of a week of training students in the school. In the third year students of physical performance level at the beginning of the school week was recorded within 1235.4 kgm / min in men and 812.5 kgm / min in girls (evaluation - above average). Conclusions : during the school week changes the physical condition typical for students in the first and second courses. In the third year students dynamic performance curve has a descending character. Do senior students - ascending- descending.